Characterization of spatiotemporal couplings with far-field beamlet cross-correlation. (1st November 2022) - Smartsev, Slava; Tata, Sheroy; Liberman, Aaron; Adelberg, Michael; Mohanty, Arujash; Levine, Eitan Y; Seemann, Omri; Wan, Yang; Kroupp, Eyal; Lahaye, Ronan; Thaury, Cédric; Malka, Victor
Abstract: We present a novel, straightforward method for the characterization of spatiotemporal couplings (STCs) in ultra-short laser pulses. The method employs far-field interferometry and inverse Fourier transform spectroscopy, built on the theoretical basis derived in this paper. It stands out in its simplicity: it requires few non-standard optical elements and simple analysis algorithms. This method was used to measure the space-time intensity of our 100 TW class laser and to test the efficacy of a refractive doublet as a suppressor of pulse front curvature (PFC). The measured low-order STCs agreed with ray-tracing simulations. In addition, we demonstrate a one-shot measurement technique, derived from our central method, which allows for quick and precise alignment of the compressor by pulse front tilt minimization and for optimal refractive doublet positioning for the suppression of PFC.